Pendampingan Pembuatan Plang Edukasi Lamanya Sampah Anorganik Terurai di Desa Wagir Lor Kecamatan Ngebel - Ruhana Nur Fadilah; Nafi'ah (Social Science Academic, 2025)
Inorganic waste is a serious problem in rural areas as it takes hundreds to thousands of years to decompose. The lack of public awareness regarding the long-term impacts of plastic, glass, cans, and styrofoam waste worsens environmental conditions, especially with limited information and waste management facilities in villages. This study is a community service activity based on environmental education aimed at raising the awareness of Wagir Lor Village residents, Ngebel Sub-district, about the dangers of inorganic waste through a visual medium in the form of educational signboards. The program was carried out from July to August 2025, involving village officials, youth groups, and local residents. The method included observation, signboard design, socialization, production and installation of the boards, and evaluation of community responses. The boards provided information about the decomposition period of inorganic waste, such as plastic (50–100 years), cans (80–200 years), glass (up to thousands of years), and styrofoam (more than 500 years). The results indicated that most residents still disposed of waste carelessly, but the presence of educational boards attracted considerable attention. Observations showed that around 70% of the residents read and paid attention to the information, indicating an increased curiosity and awareness of the long-term effects of waste. Community participation was also evident through the involvement of village officials, youth organizations, and schoolchildren in the installation process. The implication of this activity was an improvement in environmental awareness, marked by the early practice of waste separation and the emergence of collective concern for a cleaner village. Thus, educational signboards proved to be an effective, simple, and sustainable medium for fostering environmental awareness at the village level. Further programs such as waste banks and recycling training are recommended to strengthen the long-term impact of this initiative.